Taxonomy of Diamesa steinboecki group (Diptera: Chironomidae: Diamesinae), with description and DNA barcoding of new species. I. Subgroups steinboecki and longipes - Makarchenko, Eugenyi A.; Semenchenko, Alexander A.; Palatov, Dmitry M. (Zootaxa, 2022)
The results of a revision of the Diamesa steinboecki group, namely soubgroups steinboecki and longipes (Diptera, Chironomidae, Diamesinae) are presented. Illustrated descriptions of the adult male of D. dragani sp. nov. from Sayan Mountains, D. kownackii sp. nov. from Wrangel Island, D. maisaraensis sp. nov. from Pamir, D. marinskiyi sp. nov. from Tian-Shan, D. zagrosica sp. nov. from Iran, D. moubayedi sp. nov. from Lebanon are provided with redescriptions of D. steinboecki Goetghebuer from Pamir, French and Swiss Alps, D. sakartvella Kownacki et Kownacka from Caucasus and D. praecipua Sæther et Willassen from Himalayas. Taxonomic remarks with data on the ecology and biogeography of the investigated species are given. In addition to taxonomic information, 658-bp fragments of the mitochondrial cytochrome oxidase subunit I gene from the eight species are presented and the results of DNA barcoding are discussed. Previous investigations focused to integrative taxonomy and molecular analysis of the Diamesa species collected in various mountain regions such as Alps, Tien Shan and Pamir. In the present work, we focused on the principle of considering morphological groups, giving more emphasis respect to the division in geographical areas.